2012
DOI: 10.1155/2012/568950
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Annotation of Genome-Wide ER-Regulated Genes in Breast Cancer Based on ChIP-Seq Data

Abstract: Estrogen receptor (ER) is a crucial molecule symbol of breast cancer. Molecular interactions between ER complexes and DNA regulate the expression of genes responsible for cancer cell phenotypes. However, the positions and mechanisms of the ER binding with downstream gene targets are far from being fully understood. ChIP-Seq is an important assay for the genome-wide study of protein-DNA interactions. In this paper, we explored the genome-wide chromatin localization of ER-DNA binding regions by analyzing ChIP-Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…ChIP-seq assays have confirmed these evidences as presented in studies of AR in prostate cancer cell [127,128] and of ER [129][130][131], GR [132], and PPAR [133] in breast cancer cells. In these investigations authors found new insights into the DNA sequences, in which ones NRs can bind and identify cooperating transcription factors.…”
Section: Chromatin Immunoprecipitation Sequencing (Chip-seq)supporting
confidence: 65%
“…ChIP-seq assays have confirmed these evidences as presented in studies of AR in prostate cancer cell [127,128] and of ER [129][130][131], GR [132], and PPAR [133] in breast cancer cells. In these investigations authors found new insights into the DNA sequences, in which ones NRs can bind and identify cooperating transcription factors.…”
Section: Chromatin Immunoprecipitation Sequencing (Chip-seq)supporting
confidence: 65%
“…This algorithm was chosen because (i) it has been designed for multi-class testing among RNA-seq datasets (i.e. allows for more than pair-wise comparisons simultaneously, and can identify over-expression in multiple tissues), (ii) it has been shown to have low bias and false discovery rates relative to other differential expression algorithms for other RNA-seq datasets [22] , [23] , [24] , and (iii) it has demonstrated effectiveness in other studies [21] , [25] , [26] , [27] , [28] . This algorithm identified approximately 69% of the expressed genes as being over-expressed in at least one of the tissues (with p≤0.05 confidence and a false discovery rate of 0.8%).…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we mapped the genes uniquely regulated by candidate miRNAs to GeneGo database for analysis of enriched signaling pathway and disease ontology [ 40 42 ]. GeneGo database was from MetaCore.…”
Section: Methodsmentioning
confidence: 99%